The use of an alternative feed additive, containing benzoic acid, thymol, eugenol, and piperine, improved growth performance, nutrient and energy digestibility, and gut health in weaned piglets - Silva Junior, Claudio D. [UNESP]; Martins, Claudia C. S.; Dias, Francine T. F.; Sitanaka, Natalia Y.; Ferracioli, Leticia B.; Moraes, Jose E.; Pizzolante, Carla C.; Budino, Fabio E. L.; Pereira, Rafaela; Tizioto, Polyana; Paula, Vinicius R. C.; Coutinho, Luiz L.; et al. (Oxford Univ Press Inc, 2020)
This research evaluated a feed additive (benzoic acid, eugenol, thymol, and piperine), associated or not with colistin, in weaned piglets feeding. The parameters evaluated were growth performance, apparent total tract digestibility (ATTD) of nutrients, diarrhea incidence, intestinal morphology, relative weights of digestive organs, microbial diversity, and the percentages of operational taxonomic units of microorganisms in the cecum content of pigs. One-hundred and eight crossbred piglets (5.3 +/- 0.5 kg) were used in a three-phase feeding program (21 to 35, 36 to 50, 51 to 65 d of age) and fed a control diet with no inclusion of growth promoter feed additive, a diet with 40 ppm of colistin, a diet with 0.3% of alternative additive, and a diet with 0.3% of alternative additive and 40 ppm of colistin. The diets were based on corn, soybean meal, dairy products, and spray-dried blood plasma and formulated to provide 3.40, 3.38, and 3.20 Mcal of ME/kg and 14.5, 13.3, and 10.9 g/kg of digestible lysine, in phases 1, 2, and 3, respectively. The piglets were housed three per pen, with nine replicates per diet, in a complete randomized block design based on initial BW. The data were submitted to ANOVA and means were separated by Tukey test (5%), using SAS. Pigs fed diets with the alternative feed additive had greater (P < 0.05) ADG (114.3 vs. 91.8 g) and ADFI (190.1 vs. 163.3 g) in phase 1 than pigs fed diets without the product. The alternative additive improved (P < 0.05) ATTD of crude protein (CP) in phase 1 (71.0% vs. 68.6%), gross energy in phases 1 (77.4% vs. 75.2%) and 3 (79.0% vs. 77.1%), and dry matter in phase 3 (79.1% vs. 77.1%). The antibiotic inclusion in the diets increased (P < 0.05) ATTD of CP in phase 1 (71.5% vs. 68.2%). The alternative feed additive tended (P = 0.06) to increase (46%) normal feces frequency, decreased (P < 0.05) goblet cells count (104.3 vs. 118.1) in the jejunum, and decreased (P < 0.05) small intestine (4.60% vs. 4.93%) and colon (1.41% vs. 1.65%) relative weights, compared with pigs not fed with the alternative additive. There was a tendency (P = 0.09) for a lower concentration of Escherichia-Shigella (1.46% vs. 3.5%) and lower (P < 0.05) percentage of Campylobacter (0.52% vs. 10.21%) in the cecum content of piglets fed diets containing essential oils and benzoic acid compared with pigs fed diets without the alternative feed additive. The alternative feed additive was effective in improving growth performance, diets digestibility, and gut health in piglets soon after weaning.
Keywords: diarrhea; gut health; microbiota; phytogenic additive